Effects of fiscal decentralization on regional economic growth and inequality in Indonesia - Ang, Clement Zichri (2009)
This paper looks into the background of the “Big Bang” decentralization program in Indonesia and events leading to its implementation in 2001. Effects of this decentralization on economic growth and income inequality are then analyzed for the period 1990 to 2007. The Production Function model is employed to study the effects of this fiscal decentralization on economic growth in both the provincial and district level. And, the regression results show that fiscal decentralization contributes to economic growth in Indonesia. On the other hand, the analysis of fiscal decentralization on income inequality shows that income disparities increase with decentralization.